Analisis Kinerja Pegawai Dinas Lingkungan Hidup Kabupaten Purbalingga dan Banyumas : Peran Lingkungan Kerja, Disiplin Kerja, dan Komunikasi Interpersonal - Zein, Ines Putri Adna; Bagis, Fatmah; Purwidianti, Wida; Kharismasyah, Alfato Yusnar (JURNAL ILMIAH EDUNOMIKA, 2024)
This research has respondents who are dominated by employees with civil servant status, the age of the respondents is dominated by the age range â‰¥ 10 years. Employees who have an educational history of up to a bachelor's degree also dominate the respondents, and employees who have worked for â‰¥ 10 years also dominate the respondents. In this study, studyers tested the influence of the work environment, work discipline and interpersonal communication on employee performance at the Environmental Service of the Environmental Service of Purbalinga Regency and Banyumas Regency. A good work environment will improve employee performance in both agencies. With operational discipline, agency goals will be achieved more quickly and employee performance will increase. Then, effective interpersonal communication will increase work morale and ensure employee performance leads to maximum results. Apart from the work environment, work discipline and interpersonal communication also have a significant positive influence on employee performance. Keywords: Work Environment, Work Discipline, Interpersonal Communication, Employee Performance